Kesulitan Guru dalam Menerapkan Model-Model Pembelajaran Berdasarkan Kurikulum 2013 di Sekolah Dasar - Fransiska, Wulandari; Ain, Siti Quratul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to describe Teacher Difficulties in Applying Learning Models based on the 2013 Curriculum at SDN 13 Belutu. This type of research is descriptive qualitative research. The subjects of this study were the principal and 3 classroom teachers at SDN 13 Belutu. Data collection techniques used are interviews, observation and documentation. The data analysis technique uses the Milles and Huberman model with stages, data reduction, data presentation, and concluding. The results showed that at SDN 13 Belutu the teacher had implemented a learning model that was by the 2013 curriculum. The learning model used by the teacher was the Discovery Learning model and the Problem Based Learning model. The teacher's difficulty in applying the Discovery Learning learning model is the use of time. Because during the Covid-19 pandemic, the learning time is very short compared to before the pandemic. Furthermore, the difficulty of the teacher in applying the Problem Based Learning model is that the teacher has difficulty in allocating time and determining problems that are by the learning material when they want to use the Problem Based Learning model. And the last is the teacher's difficulty in implementing the Project-Based Learning model. The teacher has difficulty in determining the material and choosing the right time so the teacher does not use the Project-Based Learning model in the learning process.